Effect of silicone based softener on fabric handle properties made by ring, rotor and MVS yarns. Issue 4 (10th July 2021) - Anam, Wardah; Akhtar, Khurram Shehzad; Ahmad, Faheem; Rasheed, Abher; Rasheed, Abher; Mohsin, Muhammad; Azam, Farooq; Ullah, Tehseen; Ahmad, Sheraz
Abstract : Purpose: The purpose of this study was to produce yarns from three different spinning techniques, i.e.Murata Vortex Spinning (MVS) ring spinning and rotor spinning. Those yarns were then used to produce fabrics. Then, the effect of silicone softener on tactile comfort of fabric was investigated. Design/methodology/approach: Three different yarns, i.e. Ring, Rotor and MVS yarns, were used to make fabrics using CCI sample loom which were then subjected to post treatments like desizing, scouring and bleaching. After the completion of the dyeing process, silicone-based softener was used to improve the hand feel of fabrics. The structures of three yarns were evaluated using Scanning electron microscopy. The fabrics were evaluated against compression, bending and surface properties using Kawabata evaluation system. Findings: The fabric made of MVS yarn depicted more geometrical roughness, coefficient of friction and bending rigidity but less compressibility as compared to fabrics made with other yarns. It was observed that softener concentration has a direct relationship with thickness and bending rigidity of the fabric, and inverse relationship with coefficient of friction and geometrical roughness of the fabric. Originality/value: MVS yarn has some superior properties over rotor and ring spun yarn like high production rates, high resistance to pilling, clear appearance and stability against deformation but has disadvantage that it has less compressibility. Therefore, softener is applied on the fabric, to address this issue, so that it could also be used for apparels application.